Sepsis in pediatrics: New concepts - Baique-Sánchez, Pedro Michael (2017)
Sepsis is one of the leading causes of mortality in adults and children. It has a negative impact on the population’s health, and the expenses for the healthcare system are estimated at several billion dollars. Infant death worldwide has represented for decades a complex and progressive inflammatory disease secondary to an infectious agent, which causes tissue dysoxia and eventually cell and organ failure, without necessarily going through hypotension in the early stages but in later stages of the disease. This review updates the definitions from the Third Consensus on Definitions of Sepsis and Septic Shock and the International Surviving Campaigns, which provide us a better understanding of the pathobiology of the disease. It aims the need to use a score of organ dysfunction in children for better appraisal and prediction of mortality, and to conduct clinical trials. The objective of this article is to present the current status of knowledge of the operational definitions and to suggest of adapting the concepts in the national clinical guidelines.